2019
DOI: 10.1088/1742-6596/1191/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Structure, thermal and electrical properties of PVDF-HFP/LiBOB solid polymer electrolyte

Abstract: Solid polymer electrolyte (SPE), which is composed of poly (vinylidenefluroride-co-hexafluoropropylene) (PVDF-HFP), lithium bis(oxalate) borate (LiBOB) salt and various concentrations of TiO2 as filler, has been prepared by solution casting technique. Structure, thermal and electrical properties of the SPE were examined using XRD and SEM, TG/DSC, and impedance spectroscopy, respectively. XRD analysis reveals amorphous nature of PVDF-HFP / LiBOB and TiO2 composite matrix. SEM photographs of polymer electrolyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…Samples with various LLZNTO contents showed that porosity first dropped and then increased with increased LLZNTO from 5 to 20 wt.% (Table 1). This was because excess LLZNTO addition led to agglomeration and some pores that were filled might again reform a porous structure 25 . The minimum porosity, at 2.6% of PTLs, was attained with 15 wt.% LLZNTO content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples with various LLZNTO contents showed that porosity first dropped and then increased with increased LLZNTO from 5 to 20 wt.% (Table 1). This was because excess LLZNTO addition led to agglomeration and some pores that were filled might again reform a porous structure 25 . The minimum porosity, at 2.6% of PTLs, was attained with 15 wt.% LLZNTO content.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, inorganic fillers of garnet‐type LLZNTO containing a high concentration of Li vacancy should supply an abundant Li + transferring channel 15 . However, the conductivity of the composite electrolyte is decreased during the content of LLZNTO is over to 15 wt.%, which may be due to the aggregation of the ceramic particles in the electrolyte membrane, and thus hinder the transmission of Li ions 25 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tidak nampaknya puncak leleh SN dan terbentuknya puncak titik leleh baru atau puncak fasa transisi mengindikasikan bahwa fasa transisi SN telah terjadi perubahan fasa dari monoclinic (beraturan) menjadi fasa amorf (tidak beraturan). Temperatur leleh (T m ) SN adalah 49 ºC [19], sehingga dengan penambahan aditif SN akan meningkatkan kelarutan garam LiBOB dengan harapan dapat meningkatkan konsentrasi LiBOB. Pengujian konduktivitas dengan kondisi pengukuran pada temperatur ruang diperlihatkan seperti pada Gambar 4.…”
Section: Hasil Dan Pembahasanunclassified